Simple and Low Cost Environmentally Friendly CASWAT-G Surface Ropeway Transportation System for Mountainous Countries - Baral, Lok B.; Nakarmi, Jeevan J.; Poudyal, Khem N.; Karki, Nava R.; Nalmpantis, Dimitrios; Amatya, V. P.; Dura, Hari B.; Sah, Chandan (Amrit Research Journal, 2022)
CASWAT-G (Circulating Cable Supported up down Walking Technology by Using Gravity) is a surface ropeway transportation system. There is enormous source of gravitational potential energy (GPE) in the nature which needs particular technology to use it for daily life need. Presented technology is useful to apply in the mountainous countries that have high possibilities potential slope places it requires. The system uses simple material and low number of parts which makes the technology simple and low cost. The driving forces are: harvested force from the users and leg muscle force from them. It is a pollutionless and very less destructive to natural environment technology. The simple form of prototype has the efficiency above 80% which is best even among different ropeways and is useful to apply.